2018
DOI: 10.1111/odi.12773
|View full text |Cite
|
Sign up to set email alerts
|

Role of myofibroblasts in normal and pathological periodontal wound healing

Abstract: Myofibroblasts represent specific subpopulations of cells with important roles in tissue remodeling in both health and disease. They are not usually found in resting healthy tissues. However, they increase in number during the proliferative phase of wound healing. In these conditions, myofibroblasts secrete and organize different molecular components of the extracellular matrix that with time will reconstitute and hopefully regenerate the damaged tissue. Importantly, these cell populations must be eliminated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…The efficacy of blue light inhibiting TGFβ-induced cell differentiation has been previously reported [62]. Differentiated fibroblasts known as myofibroblasts are uncommon in healthy gingival tissue and thus blue light may regulate TGFβ-induced fibroblast differentiation by modulating TGFβ1 secretion and promoting the autocrine regulation of TGFβR1 gene expression [63].…”
Section: Discussionmentioning
confidence: 94%
“…The efficacy of blue light inhibiting TGFβ-induced cell differentiation has been previously reported [62]. Differentiated fibroblasts known as myofibroblasts are uncommon in healthy gingival tissue and thus blue light may regulate TGFβ-induced fibroblast differentiation by modulating TGFβ1 secretion and promoting the autocrine regulation of TGFβR1 gene expression [63].…”
Section: Discussionmentioning
confidence: 94%
“…Transforming growth factor-β (TGF-β) is produced in the early stages of wound healing, produced by activated macrophages and neutrophils, which act as chemotactic and mitogenic factor to gingival and periodontal ligament cells, other than to be involved in the myofibroblast differentiation (Kuru et al, 2004;Yi et al, 2016). As reported by Smith et al (2006), TGF-β1 was able to bring some modifications in the adhesive properties of hGFs and may increase the expression levels of several integrins (Rout et al, 2002;Smith et al, 2006). TGF-β1 is also considered an important factor in fibrosis regulation and in the induction of the transition of fibroblast phenotype to myofibroblast in vitro by means of the Smad 3-dependent pathway (Desmouliere et al, 1993;Fang and Svoboda, 2005;Willis et al, 2006;Hinz et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…Myofibroblasts are commonly involved in the production of ECM components, such as collagens, glycoproteins, and proteoglycans, and the augmentation of matrix elements such as laminin, glycosaminoglycans, and hyaluronic acid. In gingival tissue during the wound healing process, myofibroblasts originate from resident fibroblasts, which are stimulated by cytokines and growth factors (Rout et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Trans-differentiation from fibroblasts to myofibroblasts attracts attentions because of the important implications in wound healing, organ fibrosis, and regenerative medicine (Li and Wang, 2011;Smith, 2018;Tomasek et al, 2002). Although studies have demonstrated that TGF-b/Smad pathway is indispensible in vitro and in vivo for the process of fibroblasts trans-differentiation, the concrete mechanism is still unclear (Conte et al, 2014;Rodriguez et al, 2019).…”
Section: Discussionmentioning
confidence: 99%